A Simple HPLC Method for Chlorogenic Acid Quantification in Jiruge-6 Suppositories - Yilina; Yiran Bao; Nomin‑Erdene Ulambayar; Enkhjargal Dorjbal (Trends in Immunotherapy, 2025)
Chlorogenic acid (CGA) is a key bioactive polyphenol in Traditional Chinese Medicine (TCM) formulations including Jiruge-6 Suppositories. This study aimed to develop and validate a simple and sensitive HPLC method for quantifying CGA in these products. The optimized method utilized a C18 column with a mobile phase of acetonitrile and 0.1% phosphoric acid (15:85, v/v) at 1.0 mL/min flow rate, with detection at a 327 nm. Ultrasonic extraction with 70% methanol enhanced sample preparation efficiency. The method demonstrated excellent linearity (r² > 0.999) across the range of 1.0–100.0 μg/mL, high precision (RSD < 2.0%), and good recovery (98.2–101.5%). Detection and quantification limits were 0.30 μg/mL and 0.95 μg/mL, respectively. Analysis of five commercial batches from the same manufacturer revealed CGA content of 0.42-0.57 mg/suppository with notable seasonal variation. This validated method provides a practical approach for routine quality control of Jiruge-6 Suppositories, supporting standardization of TCM products.